2012
DOI: 10.1039/c2ee03068c
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the coupled cation interactions behind the electrochemical profile of LixNi0.5Mn1.5O4

Abstract: We present first-principles energy calculations and a cluster expansion model of the ionic ordering in Li x Ni 0.5 Mn 1.5 O 4 (0 ≤ x ≤ 1), one of the proposed highenergy density next-generation Li-ion cathode materials. The developed model predicts an intricate relationship between the preferred Li-vacancy ordering and the Ni/Mn configuration, which explains the difference in intermediate ground states between ordered (P4 3 32) and disordered (Fd3m) Ni/Mn configuration. The phase sequence as a function of lith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
127
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(142 citation statements)
references
References 38 publications
15
127
0
Order By: Relevance
“…As a result, extended solid-solution behavior in the Li-doped sample can result from the large Ni/Mn disordering. This observation agrees very well with recent calculation results, 10,11 which indicate that a perfectly cation-ordered spinel with a space group of P4 3 32 resists the solid-solution phase transition behavior because the Ni/Mn ordering is incompatible with the ordering of Li + and vacancies during delithiation, whereas the introduction of Ni/Mn disordering into the spinel structure results in a gradual increase in stability for a solid-solution reaction, especially in a lithium-rich phase such as LNMO. The degree of Ni/Mn disordering strongly increases the solid-solution reaction during delithiation.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…As a result, extended solid-solution behavior in the Li-doped sample can result from the large Ni/Mn disordering. This observation agrees very well with recent calculation results, 10,11 which indicate that a perfectly cation-ordered spinel with a space group of P4 3 32 resists the solid-solution phase transition behavior because the Ni/Mn ordering is incompatible with the ordering of Li + and vacancies during delithiation, whereas the introduction of Ni/Mn disordering into the spinel structure results in a gradual increase in stability for a solid-solution reaction, especially in a lithium-rich phase such as LNMO. The degree of Ni/Mn disordering strongly increases the solid-solution reaction during delithiation.…”
Section: Resultssupporting
confidence: 82%
“…Recent calculations have shown that the solid-solution phase transformation in the spinel results from the disordering of Ni/Mn, not from Mn 3+ ions. 10,11 However, there are no experimental data supporting this calculation because controlling the Ni/Mn disordering to optimize electrochemical performance without the presence of Mn 3+ ions has not been feasible. As a result, understanding the effect of disordering or the effect of Mn 3+ ions on electrochemical properties is experimentally very important because the decoupling of the Ni/Mn disordering from the Mn 3+ ions can help in optimizing the electrochemical performance of the LNMO spinel.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…30 The high voltage spinel Li X Mn 1.5 Ni 0.5 O 4 also undergoes at least one firstorder phase transformation; the phase-behavior of this compound is sensitive to Ni/Mn ordering on the transition metal cation sublattice, which in turn depends on the thermal history of the material. [31][32][33][34][35][36] The Li X Mn 1.5 Ni 0.5 O 4 materials tested here are prepared in a manner known to produce a disordered Ni/Mn cation arrangement, resulting in phase-behavior mirroring that of Li X Mn 2 O 4 : initial delithiation occurs through a solid solution, followed by a first-order phase transformation between two cubic phases with a linear misfit strain of ∼1.0%. When the Ni/Mn transition metals are ordered, delithiation occurs through two distinct first-order phase transformations each with a linear misfit strain of ∼1.0%.…”
Section: -24mentioning
confidence: 99%
“…The degree of transition metal ordering in the high voltage spinel with the nominal composition LiNi 0.5 Mn 1.5 O 4 is expected to affect the voltage profile and other electrochemical characteristics of the material in operating cells 15 . In ordered materials (space group P4 3 32), the Ni and Mn occupy 4a and 12d octahedral sites, respectively, whereas in the disordered variants (space group Fd3_m) the transition metals are distributed randomly over octahedral 16d sites.…”
Section: Planning Of Experimentsmentioning
confidence: 99%